2017
DOI: 10.4236/ojpsych.2017.74025
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Epileptic Drug Prescription in a Psychiatric Hospital Outpatient Clinic in Southeast Nigeria

Abstract: The optimum control of seizures requires adequate dosing of appropriately selected anti-epileptic medications. The availability of AEDs in Nigeria is limited and this constrains the prescription latitude of clinicians. This study was conducted to describe the prescribing pattern of anti-epileptic drugs in the outpatient service of a psychiatric facility in southeast Nigeria. The case records of the epileptic patients attending the outpatient clinic of a psychiatric hospital were retrieved, reviewed and data ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Fifty-two (50.5%) patients had focal seizure while fiftyone (49.5%) had generalized forms. Of these, 46 patients (44.7%) had generalized tonic clonic seizure (primarily generalized tonic clonic); followed by focal with impaired awareness (complex partial) in 33 et al, also reported similar trend in young people. This could be attributable to the prevalence of risk factors for epilepsy that occurs commonly in childhood or young people like traumatic brain injury, recurrent febrile convulsions and CNS infections like meningitis and encephalitis found to be 14.6%, 12.6% and 5.8%…”
Section: Clinical Characteristics Of Persons With Epilepsymentioning
confidence: 70%
See 1 more Smart Citation
“…Fifty-two (50.5%) patients had focal seizure while fiftyone (49.5%) had generalized forms. Of these, 46 patients (44.7%) had generalized tonic clonic seizure (primarily generalized tonic clonic); followed by focal with impaired awareness (complex partial) in 33 et al, also reported similar trend in young people. This could be attributable to the prevalence of risk factors for epilepsy that occurs commonly in childhood or young people like traumatic brain injury, recurrent febrile convulsions and CNS infections like meningitis and encephalitis found to be 14.6%, 12.6% and 5.8%…”
Section: Clinical Characteristics Of Persons With Epilepsymentioning
confidence: 70%
“…Equally, recent studies also reported carbamazepine to be more frequently used than other 22,33 AEDs.…”
Section: Clinical Characteristics Of Persons With Epilepsymentioning
confidence: 99%